2021
DOI: 10.3390/su13105475
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Influencing Factors of Study Engagement and Its Enlightenment to Education: Role of Perceptions of School Climate and Self-Perception

Abstract: Predominantly, a school provides pedagogical support to its students, though perceptions about the school’s internal environment can incessantly influence a student’s aggregated learning experience. The present study aims to investigate the impact of the campus environment on students’ study engagement and the roles of self-concept clarity and intentional self-regulation on this association. A hypothetical model about the relationship between campus perception, self-concept clarity, intentional self-regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…This suggests that students with high perception of close relationships with classmates, do more inquiry, have equal learning opportunities with other students in the classroom, are likely to plan, manage information, monitor their comprehension, use debugging strategies and evaluate their understandings which in turn leads to improved mathematics achievement. These results echo our expectations as well as previous findings from Zhou et al (2021), Fariba Mirzaei et al (2012 and Nurulhuda and Saemah (2017) which indicated that students' regulation cognition, is positively linked to their reports of closeness with their classmates and the emphasis of inquiry activities in the classroom. This finding can be justified by taking into account the quality of studentstudent relationships and the role of inquiry skill in improving the students' academic performance.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This suggests that students with high perception of close relationships with classmates, do more inquiry, have equal learning opportunities with other students in the classroom, are likely to plan, manage information, monitor their comprehension, use debugging strategies and evaluate their understandings which in turn leads to improved mathematics achievement. These results echo our expectations as well as previous findings from Zhou et al (2021), Fariba Mirzaei et al (2012 and Nurulhuda and Saemah (2017) which indicated that students' regulation cognition, is positively linked to their reports of closeness with their classmates and the emphasis of inquiry activities in the classroom. This finding can be justified by taking into account the quality of studentstudent relationships and the role of inquiry skill in improving the students' academic performance.…”
Section: Discussionsupporting
confidence: 93%
“…This finding can be justified by taking into account the quality of studentstudent relationships and the role of inquiry skill in improving the students' academic performance. According to Zhou et al (2021), a cohesive relationship can foster more supportive environment which in turn promotes interaction between students and other elements in the environment and form positive study engagement behaviors. In other words, the bond of friendship among classmates promotes a sense of togetherness to succeed in learning and encourages them to use the most effective learning strategies such as regulation cognition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orbach et al [10] found no correlation between body investment and depression-although authors suggest this lack of association may be due to limitations with sample sizes and depression measures-this non-significance may also suggest that not all body investment affects depression. This is because it is not necessarily the objective reality that affects an individual's attitude and behavior, but how they perceive their own experience [11]. Self-esteem is a person's evaluation of themself, mainly based on how much they like or dislike themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Student engagement has been defined as the physical or mental energy and effort students apply and invest in their academic environment [3]. Also, student engagement envelops the disposition and energy that students maintain in a learning process, persistence in the face of obstacles, and the value given to learning [4]. A higher level of student engagement generates deep learning, active participation, and a positive response to challenges [4].…”
Section: Introductionmentioning
confidence: 99%